DYNAMIC INTEGRATIVE CONTINUUM MODEL AS A MULTIDIMENSIONAL FRAMEWORK FOR HIDDEN INTENTION DECODING - DILBARXON SHAVKATOVNA ARSLANBEKOVA; ABDULKHAYEVA MALIKA MARATOVNA (Ta'limda raqamli texnologiyalarni tadbiq etishning zamonaviy tendensiyalari va rivojlanish omillari, 2026)
The present study investigates hidden intention as a multidimensional communicative phenomenon emerging through interaction between cognitive, psycholinguistic, pragmatic, and discourse-level mechanisms. Contemporary approaches to implicit meaning frequently remain analytically fragmented because communicative intention is often examined through isolated linguistic indicators rather than interconnected communicative processes. In response to this methodological limitation, the study proposes the Dynamic Integrative Continuum Model (DICM) as a multidimensional framework for the psycholinguistic decoding of hidden intention in discourse interaction. The research integrates psycholinguistic, cognitive, pragmatic, and discourse-oriented perspectives in order to establish a more systematic methodology for interpreting implicit meaning. The study argues that hidden intention cannot be adequately reconstructed through lexical analysis alone because communicative meaning emerges through inferential interaction between contextual implication, strategic ambiguity, evaluative positioning, discourse organization, and adaptive communicative regulation. The findings highlight the theoretical and methodological significance of the DICM framework for contemporary psycholinguistic and discourse-analytical research.
Keywords: Keywords: hidden intention, psycholinguistics, discourse analysis, DICM, pragmatic modulation, inferential communication, implicit meaning